PENGARUH DAYA TARIK IKLAN GOJEK VERSI CERDIKIAWAN TERHADAP BRAND ATTITUDE (SIKAP TERHADAP MEREK): (Survei Kepada Followers Akun Twitter @gojekindonesia) - Adelia Nurfitrianingsih (2021)
Gojek is an online-based transportation service that continues to develop its advertising strategy which one of their creative strategies includes incorporating elements of advertising appeals into their ad called Cerdikiawan. One of the goals of advertising is to generate a positive brand attitude from its audience. However, in reality, the use of advertisement appeals has generated a variety of responses from the audience, followers of the Twitter account @gojekindonesia, includes both positives and negatives. This research examines the influence of advertising appeals in Cerdikiawan ad on brand attitude towards Gojek.. This research is a quantitative research type with the data collection using a survey method involving 100 samples. The results showed that there was an influence of the advertising appeals of the Gojek advertisement on brand attitude by 61.4%.. From the analysis of the linear regression coefficient test, it is found that the regression coefficient X is 0.839 where the regression coefficient is positive, which means that the influence of the advertisement appeals has a positive effect on brand attitude, where the higher the advertisement appeals, the higher the brand attitude. The influence of the advertising appeals of the Cerdikiawan advertisement on brand attitude is by 61.4%.